Idiopathic left fascicular ventricular tachycardia in children and adolescents - Enrique Velázquez-Rodríguez; Norberto García-Hernández; Elsa Silva-Oropeza; Santiago Jiménez-Arteaga; Arturo Martínez-Sánchez; Carlos Alva-Espinoza; Felipe David-Gómez; Lucelli Yáñez-Gutiérrez (Permanyer, 2022)
Background: Idiopathic ventricular tachycardia (VT) in children with structurally normal hearts is generally unrelated to the risk of sudden arrhythmic death. Still, it may be associated with deterioration in the quality of life. VT involving the fascicular conduction system is the most typical form of idiopathic left VT. In this retrospective study, we describe the experience of the clinical presentation, catheter ablation, and long-term follow-up of left fascicular VT in children. Methods: An electrophysiological study was performed on consecutive children at a single tertiary center. Clinical fascicular left VT was induced by programmed stimulation, and catheter ablation was guided searching for Purkinje potentials. Results: We included 18 patients (0.8 patients/year): 14 (77.8%) males and four females. The mean age of the first VT episode was 8.5 ± 5 years. Intravenous verapamil administration was effective for paroxysmal fascicular VT but not for prevention of recurrences. The mean age at the time of catheter ablation was 11.1 ± 3.8 years (8 months-16 years). The mean weight was 36.8 ± 16.4 kg (8.7-58 kg). A 100% success rate was observed with catheter ablation after repeated procedures without major complications. Mean follow-up was 2.0 ± 1.2 years (1.0-4.0 years, median 1.5), with permanent success in all patients and no antiarrhythmic drug administration. Conclusions: Fascicular VT has an adverse clinical course in children. In most cases, this condition is drug refractory. Catheter ablation is successful and safe treatment and should represent the first-line approach in symptomatic children.